PENGARUH PARTISIPASI PENYUSUNAN ANGGARAN, KOMITMEN ORGANISASI, MOTIVASI KERJA, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA MANAJERIAL PADA OPD DI KABUPATEN BADUNG - I Gusti Ayu Ratih Utariani; I Gusti Agung Krisna Lestari; Sarita Vania Clarissa (Universitas Triatma Mulya, 2022)
This study aims to determine the effect of budgeting participation, organizational commitment, work motivation and leadership style on managerial performance. The population in this study were OPD employees in Badung Regency, with a sample of 81 people. The research method used in this study is quantitative research and for data analysis using multiple linear regression analysis. (2)organizational commitment has a significant positive effect on managerial performance, where the regression coefficient is 0.215 and sig 0.005. (3) work motivation has a significant positive effect on managerial performance, where the regression coefficient is 0.200 and sig is 0.001. (4) leadership style has a significant positive effect on managerial performance, where the regression coefficient is 0.449 and sig 0.014 (5) budgetary participation, organizational commitment, work motivation and leadership style have a positive and significant effect on managerial performance. The magnitude of the influence of independent variables on managerial performance is 65.8%. Suggestions that can be given by researchers are that OPD in Badung Regency in improving managerial performance should always pay attention to budgeting, organizational commitment, work motivation and leadership style